Respuesta :
The answer is -20p⁵ - 15p⁴ + 5p³
Distribute:
-5p³(4p² + 3p - 1) = (-5p³) * 4p² + (-5p³) * 3p - (-5p³) * 1 =
= (-20p³⁺²) + (-15p³⁺¹) - (-5p³) =
= -20p⁵ - 15p⁴ + 5p³
Distribute:
-5p³(4p² + 3p - 1) = (-5p³) * 4p² + (-5p³) * 3p - (-5p³) * 1 =
= (-20p³⁺²) + (-15p³⁺¹) - (-5p³) =
= -20p⁵ - 15p⁴ + 5p³
Answer:
The product of the given expression [tex]-5p^3(4p^2+3p-1)[/tex] is [tex]-20p^5-15p^4+5p^3[/tex]
Step-by-step explanation:
Consider the given expression [tex]-5p^3(4p^2+3p-1)[/tex]
We have to find the product of given expression [tex]-5p^3(4p^2+3p-1)[/tex]
Distributive property : [tex]a\cdot(b+c)=(a\cdot b)+(a\cdot c)[/tex]
Applying distributive property, we get,
[tex]-5p^3(4p^2+3p-1)=(-5p^3 \cdot 4p^2)+(-5p^3 \cdot 3p)+(-5p^3 \cdot -1)[/tex]
Simplifying further , we get,
Applying property of exponent , [tex]a^n\cdot a^m=a^{m+n}[/tex]
[tex](-5p^3 \cdot 4p^2)+(-5p^3 \cdot 3p)+(-5p^3 \cdot -1)=-20p^5-15p^4+5p^3[/tex]
Thus, the product of the given expression [tex]-5p^3(4p^2+3p-1)[/tex] is [tex]-20p^5-15p^4+5p^3[/tex]